Losartan and angiotensin II inhibit aldosterone production in anephric rats via different actions on the intraadrenal renin-angiotensin system - Peters, Jörg; Obermüller, Nicholas; Woyth, Alexander; Peters, Barbara; Maser-Gluth, Christiane; Kränzlin, Bettina; Gretz, Norbert (Endocrinology, 1999)
Angiotensin II (ANG II) is a major stimulator of aldosterone biosynthesis. When investigating the relative contribution of circulating and locally produced ANG II, we were therefore surprised to find that ANG II, given chronically sc (200 ng/kg·min), markedly inhibits a nephrectomy (NX)-induced rise of aldosterone concentrations (from 10 ± 2 to 465 ± 90 ng/100 ml in vehicle infused, and from 9 ± 2 to 177 ± 35 in ANG II infused rats 55 h after NX and hemodialysis). We further observed, by in situ hybridization, that bilateral NX increases the number of adrenocortical cells expressing renin and that this rise was prevented by ANG II. Moreover, the rise of aldosterone levels was also inhibited by the AT1-receptor antagonist, losartan (10 μg/kg·min, chronically ip from 8 ± 2 to 199 ± 26 ng/100 ml), despite the absence of circulating renin and a reduction of ANG I to less than 10%. These data demonstrate that aldosterone production, after NX, is regulated by an intraadrenal renin-angiotensin system and that this system is physiologically suppressed by circulating angiotensin.Because the effects of losartan or ANG II on aldosterone production involved a latency period of at least 30 h after NX and were associated with a modulation or recruitment of renin-producing cells, we suggest that the intraadrenal renin-angiotensin system operates via regulation of cell differentiation on a long-term scale, rather than or additionally to its short-term effects on aldosterone synthase activity.
Gesehen am 09.06.2022